THE INFLUENCE OF LIQUIDITY, EARNING MANAGEMENT AND COMPANY SIZE TOWARD TAX AGGRESSIVENESS - Arifin Arifin; Yenni Yenni; Jimmy Jimmy (Jurnal Ekonomi, 2023)
Corporate tax aggressiveness is an act of engineering taxable income that is designed through good tax planning using methods that are classified as: legal by committing tax avoidance or illegally by committing tax avoidance. In accounting, tax is one of the cost components that can reduce company profits. The amount of tax that must be paid to the state treasury depends on the amount of profit the company earns in one year. This study focuses on identifying the effect of liquidity, earnings management, and company size on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange. The independent variables involved in this study are liquidity, earnings management, and firm size, which are tested for their effect on the dependent variable, namely tax aggressiveness. Quantitative research methods are applied by analyzing the collected secondary data. The population consisted of manufacturing companies listed on the IDX, where 178 companies were selected through a purposive sampling approach. A total of 34 samples were obtained interim, from 2017 to 2021. Using the SPSS 26 program, it was revealed that liquidity has a significant effect on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange. Earnings management and company size have no significant effect on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange. Liquidity, earnings management and company size simultaneously have a significant effect on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange.